2017
DOI: 10.5194/tc-11-2883-2017
|View full text |Cite
|
Sign up to set email alerts
|

Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica

Abstract: Abstract. The ice-shelf-fringed coast of Dronning Maud Land in East Antarctica contains numerous ice rises that influence the dynamics and mass balance of the region. However, only a few of these ice rises have been investigated in detail. Here, we present field measurements of Blåskimen Island, an isle-type ice rise adjacent to Fimbul Ice Shelf. This ice rise is largely dome shaped, with a pronounced ridge extending to the south-west from its summit (410 m a.s.l.). Its bed is mostly flat and about 100 m below… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…Further east in the Fimbul Ice Shelf, three ice rises have Raymond arches, with no double lineations. Radargrams from these three ice rises, Blåskimen Island (Goel and others, 2017), Kupol Moskovskij (#2, Fig 6a), and Kupol Ciolkovskogo (#6, Fig 6b), show Raymond arches with amplitudes >0.1 H and so we classify all three as case II. Although, arches in all three ice rises are tilted and show an offset from the ice divide with the largest offset visible in Kupol Moskovskij (~0.7 km).…”
Section: Past Stability Of Dml Ice Risesmentioning
confidence: 80%
See 2 more Smart Citations
“…Further east in the Fimbul Ice Shelf, three ice rises have Raymond arches, with no double lineations. Radargrams from these three ice rises, Blåskimen Island (Goel and others, 2017), Kupol Moskovskij (#2, Fig 6a), and Kupol Ciolkovskogo (#6, Fig 6b), show Raymond arches with amplitudes >0.1 H and so we classify all three as case II. Although, arches in all three ice rises are tilted and show an offset from the ice divide with the largest offset visible in Kupol Moskovskij (~0.7 km).…”
Section: Past Stability Of Dml Ice Risesmentioning
confidence: 80%
“…The dome-shaped Blåskimen Island Ice Rise (#695) lies at the calving front west of Jutulstraumen Glacier, elevated ~350 m above the surrounding ice shelf and grounded on a nearly flat bed 100 m below sea level (Goel and others, 2017). Vega and others (2016) analyzed a 20-m-long firn core drilled at the summit, finding an SMB average of 0.70 m weq a −1 between 1996 and 2013.…”
Section: The Dml and Enderby Land Coastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conway et al, 1999;Martín et al, 2006Martín et al, , 2014, and ice-rise residence time (e.g. Drews et al, 2013Drews et al, , 2015Goel et al, 2017). Common to all these studies is the comparison of the observed isochrones derived from radar data, with the predicted age fields from models with varying input scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…1). Goel and others (2017) found that this ice rise is currently thickening, and also that the present summit has been stable for at least the past ~600 years. We test several hypotheses to elucidate the onset of recent thickening and past changes in surface mass balance (SMB).…”
Section: Introductionmentioning
confidence: 91%